IMPLEMENTASI KEBIJAKAN ANGKUTAN PERBATASAN TERINTEGRASI BUSWAY (APTB) DI PROVINSI DKI JAKARTA - mustika sari, dzauqulazali noor; ., fitriyah; taufiq, ahmad (Journal of Politic and Government Studies, 2016)
Traffic jam is a complex problem which has been faced by DKI Jakarta Province. The high rate of using private transportation in DKI Jakarta makes the condition of capital city of Indonesia is more crowded, but commuter people who live in buffer zone of DKI Jakarta (Bodetabek) also make the roads more crowded by their private transportation which used to DKI Jakarta. Many ways have been done by local government to decrease the total private transportation which enter DKI Jakarta, such as by repairing all mass transportation to mobilize people to move from private transportation to mass transportation. This research aims to see how is the implementation of APTB operational in DKI Jakarta Province also analyze what are problems faced by APTB.This research uses qualitative research method with descriptive analysis approach. Source of data which are used coming from primary and secondary data. Informant decision was done by snowball sampling method. The researcher uses two methods in collecting data,which are interview and literary study. This research is done in Communication and Transportation Department DKI Jakarta also busway stop.In 2012, Government of DKI Jakarta Province collaborate with Local Government of (Bogor, Bekasi, Tangerang) City have had cooperation to launch APTB which is integrated with busway track, so people can enjoy the facilities comfortably, without facing traffic jam. In early of launching this APTB, people accept well and run well. After almost 4 years APTB runs, there are so many problems are found in body of this APTB. Researcher finds 3 main problems which are faced by APTB, there are about license, an option given by government to operator which is disadvantageous and grant vehicles given by Ministry of Transportation.APTB is a mass transportation which is needed by capital people. However, because of many problems which are faced, government should look for the best solution for APTB operational, so that people can enjoy the service safely and comfortably, without facing conflict that makes people confused.Keywords: Traffic Jam, Commuter, Mass Transportation, APTB.